‘Belakang’ dan ‘Halus’: Politik Keiburumahtanggaan Perempuan - Eka Chandra (Antropologi Indonesia, 2010)
This article examines the dynamic of poor women identities in Boyolali through their knowledge on needs, ways to meet needs, means of expressing interest, and how local leaders facilitating aspirations of the poor. There is knowledge diversity and pattern of political action among the women in encountering poverty-related hardship in the daily lives. This study emphasizes the need to understand diversity of poor women to elaborate women, household and the poverty issues.